Incarceration and Addiction: Women’s Lived Experiences of Deprivation - Chiao-Yu Yang (Societies)
Aims: This research examined the incarceration experiences of adult women with histories of drug addiction, aiming to fill knowledge gaps regarding how these women subjectively interpret their incarceration experiences. Methodology: In-depth interviews were conducted with 22 formerly incarcerated women from the Northeast and Midwest United States. A phenomenological approach was used to explore the meaning of incarceration for the participants, with the deprivation model of imprisonment guiding the analysis. Findings: Women with drug addiction reported being treated differently while incarcerated because of their addiction. They experienced a lack of physical and psychosocial security, limited autonomy in health-related decisions, and diminished freedom to act and express themselves, often as a result of their mental health and drug addiction issues. Additionally, they experienced a loss of identity, stigma, and internalized stigma due to the way they were treated in prison. Conclusions: Incarceration is a critical life event that deprives women of many basic human needs, shaping their health, self-perception, and understanding of the criminal justice system. Further research is necessary to explore how the experience of incarceration impacts women’s mental health, drug addiction recovery, and overall well-being.